Parvovirus B19 infection prevalens in North-West Russia - A. Y. Antipova; I. N. Lavrentieva; M. A. Bitchourina; L. V. Lialina; F. R. Koutoueva (Журнал инфектологии, 2014)
The aim of this study is to estimate parvovirus B19 (PV B19) infection (infectious erythema) prevalence in North-West Russia. In 2009-2011 anti-IgM antibodies against PV B19 among 12,5% of patients with exanthematous disease was detected in 9 (from 11) administrative territories of N-W region. Prevalence of anti-IgG antibodies in pregnant females (risk group) vary from 37,5 to 83,3%% in various age groups. Sufficient that most reproductively active females age group (18–35 yo) belongs to the group of risk: 49,2% (in St-Petersburg) and 40,5% (in Vologda) were anti-IgG PV B19 negative. Rational clinical laboratory diagnostics and modern surveilliance of PV B19 and other exanthematous diseases were discussed.